Effect of Tila Taila Shirodhara in Anidra - A Case Series (AYUSHDHARA, 2023)
People with insomnia, commonly referred to as sleeplessness, have problems falling asleep. Around 10% to 30% of individuals experience insomnia at any given moment, and up to 50% of people experience it in the course of a single year. Only 6% of people develop insomnia that lasts longer than a month and is unrelated to any problem. The typical first line of treatment are Sleep hygiene and lifestyle changes but is restricted only to the mild cases, Moderate or severe cases requires medications like sleeping pills, sedatives, antidepressants, antipsychotic drugs like Antihistamines, Benzodiazepines etc. The side effect, dependency and withdrawal symptoms of these drugs are not new to the medical sciences. On the antagonistic part Ayurveda can provide a safe and effective non interventional solution to it by Shirodhara a Panchakarma therapeutic measure. In this case series Tila Taila Dhara was used to see the effect on various criteria like Athens Insomnia Scale Hamilton Anxiety Scale, Hamilton Depression Scale, WHO - Quality of scale (Bref) and Ayurveda Lakshana and an overall improvement of 74.9 % was found in all these criteria’s which was found worth sharing to the medical fraternity for enhancement and its further appraisal.